2018
DOI: 10.4314/jfas.v9i6s.94
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of badminton game instructions effect of non-linear pedagogy and linear pedagogy

Abstract: The recent implementation of TGfU pedagogy among Malaysian schools game curriculum challenging teachers who are comfortable with technical-skill driven Linear Pedagogy (LP).This conundrum led to this quasi experimental pre-post-test design study using n = 56 students aged 13±.23 years old investigated Non Linear Pedagogy (NP) and LP models using badminton curriculum in terms of tactical decision making, recovery movement to base, skill execution of drop shots and smash in badminton doubles game play. Findings,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Finally, the results obtained in this study are consistent those of previous studies in which non-linear pedagogy was applied practically and experimentally [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The use of constraint manipulations, whereby actions are limited, and objectives are forced, promoted the development of motor behaviours and tactical decisions of the participating subjects during each exercise despite not having requested them, indicating the effectiveness of the method in achieving the motor goal.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, the results obtained in this study are consistent those of previous studies in which non-linear pedagogy was applied practically and experimentally [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. The use of constraint manipulations, whereby actions are limited, and objectives are forced, promoted the development of motor behaviours and tactical decisions of the participating subjects during each exercise despite not having requested them, indicating the effectiveness of the method in achieving the motor goal.…”
Section: Discussionsupporting
confidence: 91%
“…Estos hallazgos, sugieren que el proceso de entrenamiento de las acciones propias de los deportes colectivos sea predominantemente implícito y no consciente, en lugar de explícito y consciente tal y como se concibe en las metodologías tradicionales (Balagué et al, 2014). En las metodologías tradicionales predominan tareas de entrenamiento excesivamente analíticas y estructuradas (Robles-Rodríguez, Giménez & Abad, 2011), que poco se parecen a los contextos cambiantes propios del partido; este hecho ha sido, y sigue siendo, objeto de debate pues surgen dudas respecto a la transferencia de los aprendizajes adquiridos en este tipo de tareas (Chow & Atencio, 2014;Nathan, Salimin, & Shahril, 2017;Seirul•lo, 2017).…”
Section: Introductionunclassified
“…Furthermore, only two studies in a physical education context and one in a formal badminton competition have provided information on player learning when playing with scaled equipment and play spaces. The study developed by Nathan et al [ 38 ] compared the NLP and Linear Pedagogy (LP) models during a badminton competition in students of approximately 13 years. The results showed that NLP improved the students’ game performance in terms of their tactical decision-making, recovery movement to base and skills execution regarding drop shots and smashes, as compared to LP.…”
Section: Introductionmentioning
confidence: 99%